Considerations for member states implementing the EU supply chain regulation - Gabriel Felbermayr; Klaus S. Friesenbichler (EconPol Forum, 2024)
The EU Corporate Sustainable Due Diligence Directive shifts the costs of compliance with social and environmental rules to private entities within complex supply networks.To ensure effective and cost-efficient implementation, the Directive should aim to reduce economic complexity. Regulations should exempt countries with strong regulatory systems. Public agencies should establish harmonized standards, and organize a private certification scheme that focuses on suppliers rather than the entire network. The new European Parliament may need to adjust the legal framework accordingly.
Keywords: 330